Índice de prioridad de seguridad eléctrica para equipo médico (IPSEEM) - Ortiz-Posadas, M. R.; Vernet-Saavedra, E. A. (Revista Mexicana de Ingenieria Biomedica, 2007)
Due to the wide variety of equipment existing in clinical areas, there is an important question: which and how often electrical safety tests most be applied to the medical equipment. There are important differences about the electrical safety, such as the electrical insulation or the hazard considering the connection between patient and electrical instrumentation. The objective of this work was to develop an electrical safety priority index for medical equipment (ESPIME) involving different classifications related with electrical safety, in order to provide a numeric code indicating the priority and frequency for applying the electrical safety tests to medical equipment. The index were applied to the medical equipment in critical care locations and the result, were used to defined which set of medical equipment would be the first for developing and applying electrical safety tests in a private hospital in Mexico City.